Covenant, Compassion and Marketisation in Healthcare: the mastery of Mammon and the service of grace - Hordern, J (Routledge, 2018)
This chapter argues that covenantal thought and practice has the capacity to discipline marketisation processes in service of an ethos of gracious compassion in healthcare. It engages critically with the analyses of Diagnosis Related Groups, Personal Budgets and Defensive Medicine offered by Feiler, Herring, Papanikitas and Jani in the preceding three chapters, showing that the key themes of ‘care’ and ‘work’ can be illumined by a covenantal approach which works judiciously with healthcare marketisation. Constructively, it draws on parallels in the Armed Services to argue for five required characteristics of a written and institutionalised Healthcare Covenant between health and care workers and the public. Drawing on traditions of pastoral and political theology to explore the psychological and social influences of marketisation, this chapter provides the bridge between the systemic issues of Part I, the policy concerns of Part II and the questions of professional ethics considered in Part III.